2003
DOI: 10.1073/pnas.2035060100
|View full text |Cite
|
Sign up to set email alerts
|

Estimating mean lifetime

Abstract: The life expectancy implied by current age-specific mortality rates is calculated with life table methods that are among the oldest and most fundamental tools of demography. We demonstrate that these conventional estimates of period life expectancy are affected by an undesirable ''tempo effect.'' The tempo effect is positive when the mean age at death is rising and negative when the mean is declining. Estimates of the effect for females in three countries with high and rising life expectancy range from 1.6 yr … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(43 citation statements)
references
References 12 publications
(4 reference statements)
3
39
0
Order By: Relevance
“…Bongaarts and Feeney (2002Feeney ( , 2003 showed that the value of µ(0, t) declines over time. When the reduction in mortality is almost negligible, and the value of µ(0, t) approaches zero, equations (6) and (7) decrease to a constant number of survivors…”
Section: Gompertz Mortality Change Modelmentioning
confidence: 99%
“…Bongaarts and Feeney (2002Feeney ( , 2003 showed that the value of µ(0, t) declines over time. When the reduction in mortality is almost negligible, and the value of µ(0, t) approaches zero, equations (6) and (7) decrease to a constant number of survivors…”
Section: Gompertz Mortality Change Modelmentioning
confidence: 99%
“…The story of the "life extension" pill discussed by Bongaarts and Feeney (2003) illustrates the potential advantages of tempo-adjustment in the case of a sudden shift in survival. (See Figure 1a.) On January 1, everyone in a previously stationary population takes a pill postponing their previously programmed date of death by 3 months.…”
Section: A Single Magic Pillmentioning
confidence: 99%
“…Here there is no debate. Bongaarts andFeeney (2002 and2003) Bongaarts & Feeney (2003) figure 6 shows the last 15 years of this series. Linearity in CAL implies linear shifts.…”
Section: Which Scenario Is More Realistic?mentioning
confidence: 99%
“…As shown here, CAL is also approximately equal to certain measures of mean lifespan for the population in question. For example, it is quite similar in form to 0 e′ , defined to be the mean age at death (MAD) that would be observed in a given time period for a population with an identical historical mortality pattern and a constant annual number of births (Bongaarts and Feeney, 2003). However, such measures describe population dynamics, not the life course of a synthetic cohort based exclusively on the mortality risks of a given period.…”
Section: Population Dynamics Vs Synthetic Cohortsmentioning
confidence: 99%